1981
DOI: 10.1111/j.1365-2427.1981.tb01268.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three mapping procedures developed for river macrophytes

Abstract: Three methods of mapping macrophytes on short sections of river are described and compared. All methods involve setting up a l-m grid system over the site using permanent stakes to locate a series of temporary strings. The first method (detailed mapping), which generates a map. uses the grid system to locate accurately the position of macrophytes and substrata on the river bed. It is very time consuming and objectivity in mapping is difficult to achieve. The second method (points method) involves recording the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(13 citation statements)
references
References 7 publications
3
10
0
Order By: Relevance
“…In this study the removed material as a proportion of the macrophyte biomass in a reach was negligible; even where macrophyte biomass was lowest (Maiden Newton, March) sampling-related destruction accounted for < 1.4 % of biomass within a 10 m reach. Wright et al (1981) concluded that repeated monthly sampling of chalk river macrophytes (area = 0.05 m 2 , n = 25 per month), using a similar method to this study, did not affect subsequent measures of abundance. Therefore, repeated sampling may not affect future macrophyte abundance, when both the sampler size and sample number are small.…”
Section: Discussionsupporting
confidence: 50%
“…In this study the removed material as a proportion of the macrophyte biomass in a reach was negligible; even where macrophyte biomass was lowest (Maiden Newton, March) sampling-related destruction accounted for < 1.4 % of biomass within a 10 m reach. Wright et al (1981) concluded that repeated monthly sampling of chalk river macrophytes (area = 0.05 m 2 , n = 25 per month), using a similar method to this study, did not affect subsequent measures of abundance. Therefore, repeated sampling may not affect future macrophyte abundance, when both the sampler size and sample number are small.…”
Section: Discussionsupporting
confidence: 50%
“…Finally, there is a volumetric version of the blockage factor, which relates the volume occupied by the plants to the volume of the chosen reach of channel. Fisher (1992) related both the volumetric blockage factor and the surface area blockage factor to Manning's n. Since Fisher concluded that it was actually easier to measure the surface area ratio (for mapping techniques of aquatic macrophytes, see Wright et al (1981)), she proposed that this method should be used. The best-fit relationship of this type was…”
Section: Empirical Models Of Vegetative Resistancementioning
confidence: 98%
“…This issue should be investigated in more detail, e.g. by applying the 'rectangle method' described by (Wright et al, 1981).…”
Section: Pca1mentioning
confidence: 99%